2020
DOI: 10.1186/s12875-020-01162-5
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, attitudes, barriers, and knowledge about evidence-based medicine among family physicians in Croatia: a cross-sectional study

Abstract: Background: Evidence-based medicine (EBM) aims to assist physicians in making medical decisions based on the integration of the current best evidence, clinical expertise, and patients' values. Extensive research has been conducted regarding physicians' awareness, attitudes, barriers, and knowledge about EBM. In Croatia, there is a lack of research on this topic, especially among family physicians (FP). The aim of this study was to assess the awareness, attitudes, barriers, and knowledge about EBM among FPs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Similarly, a questionnaire-based study conducted by McColl et al also stated that general practitioners had low awareness and access to the commonly used EBM databases [ 18 ]. Our findings are consistent with a recent cross-sectional survey conducted in Croatia by Nejašmić D et al They explored that less than half of the family physicians considered the major EBM database (Medline—49.1% and Cochrane library—47.1%) useful for patient care [ 23 ]. Interestingly Unadkat, M.B et al 2021 reported a good understanding of EBM among their study respondents [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, a questionnaire-based study conducted by McColl et al also stated that general practitioners had low awareness and access to the commonly used EBM databases [ 18 ]. Our findings are consistent with a recent cross-sectional survey conducted in Croatia by Nejašmić D et al They explored that less than half of the family physicians considered the major EBM database (Medline—49.1% and Cochrane library—47.1%) useful for patient care [ 23 ]. Interestingly Unadkat, M.B et al 2021 reported a good understanding of EBM among their study respondents [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…In Germany and the UK, scarce opportunities for acquiring basic research skills during undergraduate education have been reported 54. Our findings are consistent with observations from Europe, Africa, the Middle East and Latin America 48 55–58. In a survey of Latin American medical students, 67.4% reported not receiving adequate training in research and publication 58.…”
Section: Discussionsupporting
confidence: 88%
“…Encouraging collaborative relationships between general practices is needed not only to preserve GPs' mental health but to expand the response capacity for current and future crises. Time pressure is a common stressor in general practice and negatively affects the GP seeking relevant information and reading scientific literature [31,32]. During a pandemic, increased time pressure due to a higher workload, uncertainties regarding an unknown disease, work reorganization, and potential lack of confidence in caring for COVID-19 patients might underpin additional psychological distress among GPs [33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%